2000
DOI: 10.1046/j.1365-3113.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Cladistic analysis of Coenosiini (Diptera: Muscidae: Coenosiinae)

Abstract: Summary The phylogenetic relationships among world genera of Coenosiini (Diptera: Muscidae: Coenosiinae) were investigated using parsimony. The analysis involved forty‐six ingroup terminal taxa, representing 100% of the genera currently assigned to this tribe, three outgroups and sixty‐seven adult male and female morphological characters. The monophyly of Coenosiini is confirmed by the position of the three katepisternal bristles, equidistant from each other and placed at the points of an equilateral triangle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Originally ALBUQUERQUE (1958) described the second and the third (posterior) frontal setae of the head as reclinate. This led to some discussions by subsequent authors (HENNIG 1965, COURI & PONT 2000 because in all other genera of Neotropical Coenosiini only the last pair (the third one) is reclinate and only non-Neotropical genera species of Coenosiini have the second and the third (posterior) frontal setae reclinated. After examining the holotype of P. xanthogaster we have concluded that the interpretation of AL-BUQUERQUE (1958) was wrong and that only the last pair of frontal setae is reclinate as in all other genera of Neotropical Coenosiini and,contrasting with the state found in other, nonNeotropical Coenosiini genera, in which the second and third frontal setae are clearly reclinate, and the curvature of the second seta follows the curvature of the third (Fig.…”
Section: Pilispina Pilitibiamentioning
confidence: 99%
“…Originally ALBUQUERQUE (1958) described the second and the third (posterior) frontal setae of the head as reclinate. This led to some discussions by subsequent authors (HENNIG 1965, COURI & PONT 2000 because in all other genera of Neotropical Coenosiini only the last pair (the third one) is reclinate and only non-Neotropical genera species of Coenosiini have the second and the third (posterior) frontal setae reclinated. After examining the holotype of P. xanthogaster we have concluded that the interpretation of AL-BUQUERQUE (1958) was wrong and that only the last pair of frontal setae is reclinate as in all other genera of Neotropical Coenosiini and,contrasting with the state found in other, nonNeotropical Coenosiini genera, in which the second and third frontal setae are clearly reclinate, and the curvature of the second seta follows the curvature of the third (Fig.…”
Section: Pilispina Pilitibiamentioning
confidence: 99%
“…The terminology follows MCALPINE et al (1981). Table I summarizes the valid muscid genera and subgenera of the Afrotropical Region by subfamily and the number of species based on PONT (1980) for the whole Region and COURI et al (2007) for Madagascar and other synonymies (including Ophyra Robineau-Desvoidy as a junior synonym of Hydrotaea Robineau-Desvoidy); COURI & PONT (1999, 2000 for Coenosiinae and CARVALHO et al (2005) for general classification.…”
mentioning
confidence: 99%
“…Table I. Valid Muscidae genera and subgenera of the Afrotropical Region and number of species (classification as in PONT 1980, COURI et al 2006, COURI & PONT 2000and CARVALHO et al 2005 Polietes Rondani, 1866 was not included in the key, as no material was examined and the available data in literature was not sufficient. It is represented in the Afrotropical Region by only one species -P. lardaria (Fabricius, 1781).…”
mentioning
confidence: 99%
“…In the cladistic analysis of the Coenosiinae subfamily made by COURI & PONT (2000) the genus appeared forming a clade together with Schoenomyzina Malloch, 1934;Schoenomyza and Spathipheromyia Bigot, 1884. This clade was defined by the wide frons (wider than long).…”
mentioning
confidence: 99%
“…Although most of them are well known in literature, they are mainly characterized based on non-terminalia characters, as few information about the male and female terminalia is found (COURI & PONT 2000, COURI & CARVALHO 2002.…”
mentioning
confidence: 99%